A paving algorithm for dynamic generation of quadrilateral meshes for online numerical simulations of ship manoeuvring in shallow water. (1st August 2016) - Zhou, Xueqian; Sutulo, Serge; Guedes Soares, C.
Abstract: A modified paving algorithm is presented for dynamical generation of all-quadrangle meshes for simulating hydrodynamic interaction forces acting upon ships manoeuvring in restricted waters. The so-called hybrid smoother, combining advantages of the Laplacian and angle-based techniques is proposed to achieve the balance between the computational efficiency and quality of the mesh. Special attention is paid to the accuracy and robustness of the algorithm to guarantee its flawless performance in online simulations. Consistency of the algorithm is demonstrated on numerical examples including those of one or more ships crossing a dredged channel at oblique angle. In addition, possible applications to other problems of ocean and coastal engineering are briefly discussed. Highlights: A modified paving algorithm is presented for dynamical generation of all-quad meshes. A hybrid smoother combining the Laplacian and angle-based technique is proposed. The capability and robustness of the optimized paving algorithm together with the hybrid smoother is proven. Further applications to several problems encountered in coastal engineering are also included.